Colored Voters Read: Here is one instance of the treatment the Colored People of Georgia receive at the hands of the State Democratic Party.... - (:unkn) unknown (My University, 2014)
Broadside from Georgia Democratic Party to African-American voters, in which the Democrats attempt to say that they do more for black citizens than the Republicans. The figures are for 1893, so the broadside probably dates from 1894. Uncommon Georgia, race-related ephemera.
c.1894. Georgia. #11135. U-AfAmPaper
Keywords: Integration; Segregation; Politics; Political Ads; Schools; United States--Georgia; Race Relations